1993
DOI: 10.1177/0146167293192001
|View full text |Cite
|
Sign up to set email alerts
|

"Your Mother Would Like Me": Self-Presentation in the Personals Ads of Heterosexual and Homosexual Men and Women

Abstract: This study examined self-presentation strategies in the personals ads of heterosexual and homosexual men and women. Ads were coded for physical descriptors and offers of and appeals for attractiveness, financial security, expressiveness, instrumentality, sincerity, and sexual activities. The interaction of gender and sexual orientation was often the best predictor of ad contents. Specifically, (a) gay men emphasized physical characteristics most and lesbians least; (b) heterosexual women mentioned attractivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
2
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 19 publications
5
68
2
1
Order By: Relevance
“…There is evidence, for instance, that men and women (e.g., Pines, 1998) and people of different sexualities (e.g., Gonzales & Meyers, 1993;Siever, 1994) may vary in the importance they place on particular determinants of attractiveness. Would self-monitoring have the same effect for all groups?…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence, for instance, that men and women (e.g., Pines, 1998) and people of different sexualities (e.g., Gonzales & Meyers, 1993;Siever, 1994) may vary in the importance they place on particular determinants of attractiveness. Would self-monitoring have the same effect for all groups?…”
Section: Resultsmentioning
confidence: 99%
“…This high motivation can be illustrated in how users are sometimes tempted to present themselves in idealized ways. For example, researchers have found that women have the tendency to decrease their reported weight, while men increase their reported height, and men are more likely to exaggerate their income levels (Feingold, 1990;Gonzales & Meyers, 1993;Hall et al, 2010;Harrison & Saeed, 1977;Toma & Hancock, 2010). The second process of impression management is impression construction: when people explicitly choose the impression they want to make and decide the method they will use to create it.…”
Section: Tindermentioning
confidence: 99%
“…Some studies even show that gay men show a hyper-masculine pattern of mating psychology: in their personal advertisements they stress a potential mate's physical appearance (Deaux & Hanna, 1984) and sexuality or sexiness more than heterosexual men do (e.g. Child, Low, McCormick, & Cocciarella, 1996;Gonzales & Meyers, 1993;Laner, 1977;Lumby, 1978).…”
Section: Studymentioning
confidence: 99%
“…A few studies also have explicitly compared gay men and women's mate preferences and show that gay men value a mate's physical attractiveness, sexuality, physique, athleticism and youthfulness more than lesbian women do (Bailey et al, 1994;Gonzales & Meyers, 1993;Deaux & Hannah, 1984) whereas lesbian women more than gay men value a mate's personality characteristics, such as sense of humor, intelligence, sincerity, and dominance (Gonzales & Meyers, 1993;Hatala & Prehodka, 1996), revealing a similar sex difference as among heterosexuals. However, because in their mate preferences, lesbian women seem to resemble same-sex heterosexuals less than gay men, the sex difference in mate preferences among homosexuals will probably be smaller than among heterosexuals.…”
Section: Studymentioning
confidence: 99%